1987
DOI: 10.1002/acp.2350010103
|View full text |Cite
|
Sign up to set email alerts
|

Time went by so slowly: Overestimation of event duration by males and females

Abstract: In three experiments, 469 subjects watched a short videotape of a bank robbery and later estimated the duration of the tape. Subjects invariably overestimated the durations. Accuracy of time estimation was unrelated to amount of free recall (Experiment 1) or accuracy of memory (Experiment 2). Females overestimated to a greater degree than males (Experiments 2 and 3). A more stressful version of the event produced greater overestimates than a less stressful version (Experiment 3). The relationship between induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
5

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 6 publications
9
95
0
5
Order By: Relevance
“…Increased estimation of duration People tend to overestimate the durations of both positive (Frederickx et al 2013) and negative (Loftus, Schooler, Boone, & Kline 1987b) higharousal events, sometimes by a factor of 2 or 3 (Buckhout, Figueroa, & Hoff, 1975). If two objects move at the same perceived speed, but one does so (seemingly) for longer, then people would experience it as having moved farther.…”
Section: Considering Some Alternative Explanationsmentioning
confidence: 99%
“…Increased estimation of duration People tend to overestimate the durations of both positive (Frederickx et al 2013) and negative (Loftus, Schooler, Boone, & Kline 1987b) higharousal events, sometimes by a factor of 2 or 3 (Buckhout, Figueroa, & Hoff, 1975). If two objects move at the same perceived speed, but one does so (seemingly) for longer, then people would experience it as having moved farther.…”
Section: Considering Some Alternative Explanationsmentioning
confidence: 99%
“…The modal response was 60 sec with other responses clustered at 10, 15, 20, 30,45, 90, and 120 sec. This reliance on benchmark responses, previously noted by Loftus et al (1987) (comprising 76.8% of all responses in the present study), suggests guessing by respondents to fulfill the social obligation to account for their memory of the earthquake episode. This tendency also contributes to high variances and a certain degree of sloppiness in field-generated data.…”
Section: Resultsmentioning
confidence: 86%
“…In fact, 77.8 % of our respondents described themselves using only the first four descriptors on the 8-point arousal scale (calm to uneasy). Loftus et al (1987) reported that the analysis of their subject arousal data was confined to the first two levels of the arousal scale used in their design. If a person is trying to justify hislher knowledge of the earthquake by retrospectively overestimating the time he/she spent in it, this person probably would also retrospectively downgrade hislher level of anxiety or arousal.…”
Section: Resultsmentioning
confidence: 99%
“…Loftus, Schooler, Boone, and Kline (1987) used a crude stress measure in their time perception study. The experiment was based on the observed tendency for eye-witnesses of crimes to overestimate remembered duration of the event.…”
Section: Historical Overview Summarymentioning
confidence: 99%
“…Effect size for duration judgment ratio (θ) was estimated from preliminary research and studies in the literature (Langer, Wapner, & Werner, 1961;Loftus, Schooler, Boone, & Kline, 1987;Sarason & Stoops, 1978). Effect size for biological stress measures was estimated from previous research using speech stressors and progressive muscle relaxation (Schuefele, 1999).…”
Section: Sample Sizementioning
confidence: 99%